Academic Motivation, Perceived Creativity Fostering Teacher Behavior, and Student Engagement in Online Statistics Course of Indonesian Undergraduates: An Investigation of Relations and Predictability - Astri Setiamurti; Rose Mini Agoes Salim; Frieda Maryam Mangunsong; Shahnaz Safitri; Atikah Ainun Mufidah; Maridha Normawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze the relationship and influence of academic motivation and perceived creativity fostering teacher behavior (P-CFTB) on student engagement in Statistics online learning courses in Indonesia. The research used a cross-sectional design study with a quantitative approach. Three standardized scales (academic motivation scale, perceived creativity fostering teacher index, and university student engagement inventory) were filled out by 533 psychology undergraduates who participated. All data were analyzed statistically by descriptive, correlational, and multiple linear regression tests. The results show that academic motivation and student engagement, P-CFTB and student engagement were related moderately and positively (r = 0.582, r = 0.593; p < .001, respectively). Furthermore, academic motivation and P-CFTB simultaneously affected students’ learning engagement by 48%. The result shows that when students’ academic motivation is combined with creativity fostering teacher behavior, student engagement in online learning increases.